2017
DOI: 10.1016/j.bbrc.2017.06.158
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6, C/EBP-β and PPAR-γ expression correlates with intramuscular liposarcoma growth in mice: The impact of voluntary physical activity levels

Abstract: IL-6 is an axial cytokine overexpressed in cancer to promote growth and increase resistance to anti-cancer therapies. As the application of IL-6-targeting therapies are still limited, alternative non-aggressive and adjuvant approaches, like physical activity (PA) could be useful to reverse IL-6 effects. To get more insights into liposarcoma (LS) pathophysiology, we investigated potential molecular links between IL-6 and LS growth and we tested the impact of PA on such mechanism in an orthotopic model of intram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In the second study, in a model of breast cancer in mice, 35 weeks-long moderate-intensity exercise training protected from pulmonary metastases, whereas two metastases were measured in the control group [12]. In contrast, in the third study, enhanced tumor growth and metastasis were found in voluntary running mice before (6 weeks) and after (8 weeks) inoculation with liposarcoma cells compared to sedentary mice [13]. Those contrasting results on the effects of physical activity on metastatic development nicely reflect the literature in this research area.…”
Section: Whole Metastatic Developmentmentioning
confidence: 87%
“…In the second study, in a model of breast cancer in mice, 35 weeks-long moderate-intensity exercise training protected from pulmonary metastases, whereas two metastases were measured in the control group [12]. In contrast, in the third study, enhanced tumor growth and metastasis were found in voluntary running mice before (6 weeks) and after (8 weeks) inoculation with liposarcoma cells compared to sedentary mice [13]. Those contrasting results on the effects of physical activity on metastatic development nicely reflect the literature in this research area.…”
Section: Whole Metastatic Developmentmentioning
confidence: 87%
“…Interestingly, PPARγ has often been associated to Il-6 inhibition through STAT3 inactivation (Wang et al., 2004). However, other evidence suggests that PPARγ could trigger IL-6 production in skeletal muscle (Assi et al., 2017) and other cell types and tissues (Wanichkul et al., 2003; Zhang et al., 2014). Here, our data suggest that PPARγ, whose activity has been shown to be modulated by lipid ingestion (den Besten et al., 2015), could stimulate IL-6 expression through the activation of other proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been proposed to keep the tumors inside a vascularized chamber during their growth into host mice to improve the engraftment success 39Table 1Mouse xenograft models for DDLXenograftCell linesTumor driversTime to tumor formationTreatment inhibitorsTreatment responseRef.CDXLipo246Lipo224Lipo863 RTKs 10 days-6 months(37)IB115 MDM2 / CDK4 2 weeksRG7388/palbociclib co-treatmentEffective(44)IB115PI3K/Akt/mTOR1 monthBEZ-235/RG7388 co-treatmentEffective(55)Lipo246Lipo863 AXL 1 monthAXL knockoutEffective(56)Lipo246 MET 2 weeksEMD1214063Effective(59)SW872IL-62 months(63)Lipo246miR-1553–6 weeksmiR-155 knockdownEffective(72)PDX MDM2 / CDK4 / JAK2 mutations2–6 monthsP1446A-05/ruxolitinib co-treatmentModerately effective(34)ifosfamideEffective MDM2 2–4 months(36)…”
Section: Xenograft Models Of Liposarcomamentioning
confidence: 99%
“…Especially in adipose tissue, CEBPs play a pivotal role as they regulate several biological responses like proliferation, differentiation, adipocytes maturation, and cytokines production 62. To test the potential role of IL-6 on liposarcoma pathogenesis, DDL cells were intramuscularly injected into nude mice 63. Tumor growth was then monitored in both voluntary-active or inactive mice with open or restricted access to activity-wheels to test the potential effects of physical activity on tumor progression.…”
Section: Xenograft Models Of Liposarcomamentioning
confidence: 99%